Implementation of Interactive E-Modules on Students’ Literacy and Numeracy Skills in Science Subjects at SDN 4 Abuan - Putra, I Ketut Dedi Agung Susanto; Ni Wayan Ita Drastini (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2023)
This study aims to determine (1) the effect of the application of interactive e-modules on students' literacy and numeracy skills in science subjects at SDN 4 Abuan. This type of research is a quasi-experiment with Posttest-Only Control Group Design research design. The population of this study was all students at SDN 4 Abuan. As samples in this study are class V and grade VI students. Class V was used as the experimental class and class VI as the control class. There are two types of variables in this study, namely (1) the independent variable is an interactive e-module, and (2) the dependent variable is the literacy and numeracy ability of students. Data collection was carried out using the description test method to measure students' literacy and numeracy skills. The data were analyzed by performing prerequisite tests which included normality test, homogeneity test and t-test. Based on the results of data analysis obtained, the test results of normality and homogeneity of the two groups are normally distributed and homogeneous. There is a significant influence of interactive e-modules between students who learn by applying interactive e-modules and students who learn with conventional media. This shows that students' literacy and numeracy skills in science subjects with e-module media are higher than conventional learning media.